The emergence of the information society and information threats in the Internet - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The study found that with the advent and emergence of the Internet as a specific network, a new group of rights appeared related to their use on the Internet, but there is no mechanism to protect the information rights of citizens against illegal actions of third parties. The article emphasizes that it is necessary to improve the software of the activities of the main state institutions, organizations and enterprises to prevent information threats. A new type of Internet-related threats has been identified, namely, the risks associated with protecting copyright in the Internet require an appropriate state response, and ways to improve copyright protection in the Internet are analyzed. The position on the need to implement a program to increase the media literacy of the population, the professional standards of online journalism, continue the reforms of property transparency, prevent concentration on the media market and the editorial policy of the media from the influence of political and financial groups. Other types of threats analyzed, which were actualized due to the prevalence of the network society and the availability of the Internet.